2014
DOI: 10.1185/03007995.2014.980886
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pharmacokinetics of the DPP-4 inhibitor gemigliptin when coadministered with rosuvastatin or irbesartan to healthy subjects

Abstract: Gemigliptin does not affect the PK properties of rosuvastatin or irbesartan; also, rosuvastatin and irbesartan do not affect the PKs of gemigliptin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The washout period of this study was 14 days, which is long enough to eliminate carryover effects considering previously reported half-lives of 17 h for gemigliptin, 27 h for LC15-0636, and 19 h for rosuvastatin. 9,15,21 However, one case of carryover effect for gemigliptin and rosuvastatin was observed at pre-dose in the second period after washout. However, PK analysis was performed without any adjustments because both of gemigliptin and rosuvastatin concentrations were less than 5% of C max .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The washout period of this study was 14 days, which is long enough to eliminate carryover effects considering previously reported half-lives of 17 h for gemigliptin, 27 h for LC15-0636, and 19 h for rosuvastatin. 9,15,21 However, one case of carryover effect for gemigliptin and rosuvastatin was observed at pre-dose in the second period after washout. However, PK analysis was performed without any adjustments because both of gemigliptin and rosuvastatin concentrations were less than 5% of C max .…”
Section: Discussionmentioning
confidence: 99%
“…14 According to a previous study, pharmacokinetic properties of rosuvastatin are not altered by gemigliptin and vice versa. 15 The maximum daily dose of gemigliptin approved by the Ministry of Food and Drug Safety (Republic of Korea) is 50 mg (Zemiglo ® , LG Chem. 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies also revealed that gemigliptin did not alter the pharmacokinetics of most commonly used antidiabetic agents (metformin, glimepiride, and pioglitazone), antihypertensives, and lipid lowering agents. [ 18 19 20 21 ] Ketoconazole, a CYP3A4 inhibitor, moderately increased gemigliptin exposure while it was reduced when coadministered with rifampicin, a CYP3A4 inducer. [ 22 ]…”
Section: P Harmacokinetics D Osage mentioning
confidence: 99%
“…In several drug-drug interaction studies, gemigliptin did not meaningfully alter pharmacokinetics of co-medications frequently used to treat T2DM, such as antidiabetic agents (metformin, pioglitazone, and glimepiride), and antihypertensive and lipid-lowering agents (irbesartan and rosuvastatin) [ 30 31 32 33 ]. Although co-administration of ketoconazole, a potent inhibitors of CYP3A4, resulted in a moderate increase in gemigliptin exposure (1.9-fold as total active moiety of gemigliptin), no dosage adjustment should be required when gemigliptin is co-administered with ketoconazole.…”
Section: Characteristics Of Gemigliptinmentioning
confidence: 99%